Correction of the Intermetatarsal Angle Component of Hallux Valgus Using Fiberwire-Attached Endo-buttons - Holm es, Jr., George B. (Revista Internacional de Ciencias Podológicas, 2012)
The 1st-2nd intermetatarsal angular component of the hallux valgus deformity can be corrected by an osteotomysparing technique using ultra high molecular weight polyethylene (UHMWPE) braided suture (Fiberwire, Arthrex, Naples, FL) attached endo-buttons to reduce and maintain the correction. This paper will outline the surgical approach, advantages and post-operative care necessary to implement this technique.
Keywords: Hallux valgus; Intermetatarsal angle; Endo-buttons.